Depression and Antiepileptic Drug Use Do Not Affect Eslicarbazepine Efficacy in Patients With Partial-Onset Seizures - Vinall, Maria (MD Conference Express, 2015)
In this study, the effectiveness of adjunctive use of eslicarbazepine acetate on seizure frequency in patients with partial-onset seizures was not affected by the presence of depressive or baseline antiepileptic drug therapy use.